Laboratory-scale extraction of Hildegardia barteri (Mast.) Kosterm. seed oil with different solvents, purified with membrane filtration - Adeniyi A. E.; Aremo J. O.; Oluwadare A. O.; Upendra S. (Acta Universitatis Sapientiae: Alimentaria, 2023)
The shortcomings encountered from the use of conventional methods of refining draw considerable attention when it comes to the processing of edible oils. The present invention to this effect is the usage of membrane technology, which stands out as a suitable alternative, as it offers significant advantages such as minimal chemical additions, low energy consumption, and the retention of nutrients and other desired components. This paper seeks to ascertain the quality of edible oil extracted by different solvents, refined via membrane filtration. Amounts of 25 mL of crude oil sample were extracted with three different solvents (n-hexane, ethanol, and n-hexane-ethanol blend) from seeds of Hildegardia barteri (Mast.) Kosterm. and were refined using a micro-filter of pore size of 0.45 µm and an ultrafiltration membrane with 50 kDa cut off before bleaching and deodorizing to obtain table oil. Proximate composition and elemental analyses were carried out on the table oil samples produced and compared with food-grade standards. Results obtained showed 0.133–0.53% moisture content, 0.04% ash, 98.90–99.67% ether extract, 0.23% carbohydrate, and elemental compositions of 51.60–55.00% C, 6.12–6.30% H, 6.21–6.28% O, 0.01–0.02% N, and 13.0–15.0% P for edible oil samples. The findings of this study indicate that edible oil produced from the seeds of H. barteri via membrane technology yields good-quality oil for commercial production, except for the need to enhance further reduction of phosphorus content.